Examples

Find the Expanded Form
2(x-6)2-(y-2)2=162(x6)2(y2)2=16
Step 1
Simplify the left side 2(x-6)2-(y-2)22(x6)2(y2)2.
Tap for more steps...
Step 1.1
Simplify each term.
Tap for more steps...
Step 1.1.1
Rewrite (x-6)2(x6)2 as (x-6)(x-6)(x6)(x6).
2((x-6)(x-6))-(y-2)2=162((x6)(x6))(y2)2=16
Step 1.1.2
Expand (x-6)(x-6)(x6)(x6) using the FOIL Method.
Tap for more steps...
Step 1.1.2.1
Apply the distributive property.
2(x(x-6)-6(x-6))-(y-2)2=162(x(x6)6(x6))(y2)2=16
Step 1.1.2.2
Apply the distributive property.
2(xx+x-6-6(x-6))-(y-2)2=162(xx+x66(x6))(y2)2=16
Step 1.1.2.3
Apply the distributive property.
2(xx+x-6-6x-6-6)-(y-2)2=162(xx+x66x66)(y2)2=16
2(xx+x-6-6x-6-6)-(y-2)2=162(xx+x66x66)(y2)2=16
Step 1.1.3
Simplify and combine like terms.
Tap for more steps...
Step 1.1.3.1
Simplify each term.
Tap for more steps...
Step 1.1.3.1.1
Multiply xx by xx.
2(x2+x-6-6x-6-6)-(y-2)2=162(x2+x66x66)(y2)2=16
Step 1.1.3.1.2
Move -66 to the left of xx.
2(x2-6x-6x-6-6)-(y-2)2=162(x26x6x66)(y2)2=16
Step 1.1.3.1.3
Multiply -66 by -66.
2(x2-6x-6x+36)-(y-2)2=162(x26x6x+36)(y2)2=16
2(x2-6x-6x+36)-(y-2)2=162(x26x6x+36)(y2)2=16
Step 1.1.3.2
Subtract 6x6x from -6x6x.
2(x2-12x+36)-(y-2)2=162(x212x+36)(y2)2=16
2(x2-12x+36)-(y-2)2=162(x212x+36)(y2)2=16
Step 1.1.4
Apply the distributive property.
2x2+2(-12x)+236-(y-2)2=162x2+2(12x)+236(y2)2=16
Step 1.1.5
Simplify.
Tap for more steps...
Step 1.1.5.1
Multiply -1212 by 22.
2x2-24x+236-(y-2)2=162x224x+236(y2)2=16
Step 1.1.5.2
Multiply 22 by 3636.
2x2-24x+72-(y-2)2=162x224x+72(y2)2=16
2x2-24x+72-(y-2)2=162x224x+72(y2)2=16
Step 1.1.6
Rewrite (y-2)2(y2)2 as (y-2)(y-2)(y2)(y2).
2x2-24x+72-((y-2)(y-2))=162x224x+72((y2)(y2))=16
Step 1.1.7
Expand (y-2)(y-2)(y2)(y2) using the FOIL Method.
Tap for more steps...
Step 1.1.7.1
Apply the distributive property.
2x2-24x+72-(y(y-2)-2(y-2))=162x224x+72(y(y2)2(y2))=16
Step 1.1.7.2
Apply the distributive property.
2x2-24x+72-(yy+y-2-2(y-2))=162x224x+72(yy+y22(y2))=16
Step 1.1.7.3
Apply the distributive property.
2x2-24x+72-(yy+y-2-2y-2-2)=162x224x+72(yy+y22y22)=16
2x2-24x+72-(yy+y-2-2y-2-2)=162x224x+72(yy+y22y22)=16
Step 1.1.8
Simplify and combine like terms.
Tap for more steps...
Step 1.1.8.1
Simplify each term.
Tap for more steps...
Step 1.1.8.1.1
Multiply yy by yy.
2x2-24x+72-(y2+y-2-2y-2-2)=162x224x+72(y2+y22y22)=16
Step 1.1.8.1.2
Move -22 to the left of yy.
2x2-24x+72-(y2-2y-2y-2-2)=162x224x+72(y22y2y22)=16
Step 1.1.8.1.3
Multiply -22 by -22.
2x2-24x+72-(y2-2y-2y+4)=162x224x+72(y22y2y+4)=16
2x2-24x+72-(y2-2y-2y+4)=162x224x+72(y22y2y+4)=16
Step 1.1.8.2
Subtract 2y2y from -2y2y.
2x2-24x+72-(y2-4y+4)=162x224x+72(y24y+4)=16
2x2-24x+72-(y2-4y+4)=162x224x+72(y24y+4)=16
Step 1.1.9
Apply the distributive property.
2x2-24x+72-y2-(-4y)-14=162x224x+72y2(4y)14=16
Step 1.1.10
Simplify.
Tap for more steps...
Step 1.1.10.1
Multiply -44 by -11.
2x2-24x+72-y2+4y-14=162x224x+72y2+4y14=16
Step 1.1.10.2
Multiply -11 by 44.
2x2-24x+72-y2+4y-4=162x224x+72y2+4y4=16
2x2-24x+72-y2+4y-4=162x224x+72y2+4y4=16
2x2-24x+72-y2+4y-4=162x224x+72y2+4y4=16
Step 1.2
Simplify the expression.
Tap for more steps...
Step 1.2.1
Subtract 44 from 7272.
2x2-24x-y2+4y+68=162x224xy2+4y+68=16
Step 1.2.2
Move -24x24x.
2x2-y2-24x+4y+68=162x2y224x+4y+68=16
2x2-y2-24x+4y+68=162x2y224x+4y+68=16
2x2-y2-24x+4y+68=162x2y224x+4y+68=16
Step 2
Set the equation equal to zero.
Tap for more steps...
Step 2.1
Subtract 1616 from both sides of the equation.
2x2-y2-24x+4y+68-16=02x2y224x+4y+6816=0
Step 2.2
Subtract 1616 from 6868.
2x2-y2-24x+4y+52=02x2y224x+4y+52=0
2x2-y2-24x+4y+52=02x2y224x+4y+52=0
Enter YOUR Problem
Mathway requires javascript and a modern browser.
 [x2  12  π  xdx ]  x2  12  π  xdx  
AmazonPay